2020
DOI: 10.1016/j.chest.2020.08.1676
|View full text |Cite
|
Sign up to set email alerts
|

Refining Radial Ebus: Characterizing Imaging Interpretation and Proposal for a Standardized Grading System

Abstract: Radial probe endobronchial ultrasound (R-EBUS) provides real-time confirmation of lesion localization with bronchoscopy for peripheral pulmonary lesions. "Concentric" images indicate a lesion surrounding a bronchus and "eccentric" images indicate lesion position adjacent to the bronchus. While studies have demonstrated higher diagnostic yield with concentric views, there is no clear classification system for distinguishing the two nor for the range of different views that may be observed. This study was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Chao et al conducted a study using various image features to distinguish between neoplastic and non-neoplastic lesions, such as the margin outside the lesion, homogeneity among internal echoes, hyperechoic dots and concentric circles along the echo probe. Some of these image features were identified as diagnostic markers; however, the interpretation of images remains highly subjective 25. There is a pressing need for an objective method to interpret rEBUS images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chao et al conducted a study using various image features to distinguish between neoplastic and non-neoplastic lesions, such as the margin outside the lesion, homogeneity among internal echoes, hyperechoic dots and concentric circles along the echo probe. Some of these image features were identified as diagnostic markers; however, the interpretation of images remains highly subjective 25. There is a pressing need for an objective method to interpret rEBUS images.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these image features were identified as diagnostic markers; however, the interpretation of images remains highly subjective. 25 There is a pressing need for an objective method to interpret rEBUS images. This study demonstrated the efficacy of the proposed CNN prediction model in differentiating between malignant and benign lesions during bronchoscopic biopsy.…”
Section: Discussionmentioning
confidence: 99%